Implementasi Hak Anak Melalui Sekolah Ramah Anak di Sekolah Dasar - Retnasari, Lisa; Suprastio, Suprastio (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Y, 2024)
This study aims to describe the implementation of children's rights through child-friendly schools at Sekolah Dasar and to find out the supporting and inhibiting factors for the implementation of children's rights through child-friendly schools at Sekolah Dasar. This study uses a descriptive qualitative approach. Data collection techniques were observation, interviews, and documented. Subjects are school principals, teachers in charge of SRA, and students. The object of research is the implementation of children's rights through child-friendly schools at Sekolah Dasar. Test the validity of source triangulation and technique triangulation. Data analysis techniques of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of children's rights through child-friendly schools is carried out in 5 stages of child-friendly schools, namely the preparation stage, the planning stage, the implementation stage, the monitoring stage, and the evaluation stage which is carried out once every 3 months in the middle of the semester. Supporting factors are school quality, motivation and enthusiasm and sense of responsibility. While the inhibiting factors are the lack of land and funding, the lack of a team of child-friendly experts and the lack of outreach and training about child-friendly schools.